The political economy of inequality - Goodwin, Neva R., ed.; Dougherty, Laurie, ed. (Washington, D.C : Island Press, 2000)
Economics
Keywords: Political economy; Economics - Moral aspects; Welfare economics; Distributive justice; Corporate pow er; Poverty; Inequality; International trade